Community Empowerment Model Through the P4GN Program to Develop a Drug-Threat-Responsive - Sukmana, Cucu; Kamil, Mustofa; Ardiwinata, Jajat Sudrajat; Sulistiono, Eko; Mutamam, Mohamad Hadi Ali; Inoue, Hiromu (Journal of Nonformal Education, 2026)
Background – Drug abuse poses a serious threat to social stability and community well-being, particularly in the urban areas of Cimahi City. Research Urgency – Cimahi City requires a community-based response that mobilizes institutions and residents through the P4GN program. Research Objectives – This study aims to develop a community empowerment model through the Prevention and Eradication of Drug Abuse and Illicit Trafficking Program (P4GN) as an effort to realize a Cimahi City that is responsive to drug threats. Research Method – The study employed a qualitative descriptive method involving seven informants (one Head of BNN Cimahi City, two program outreach analysts, and four community representatives) selected purposively, using in-depth interviews, participatory observation, documentary study, and Focus Group Discussions (FGDs), with data validity examined through technique triangulation. Research Findings – The findings indicate that community empowerment through the P4GN program has the potential to be effective in increasing public awareness and knowledge of the dangers of drugs. These findings were obtained through analysis of data from interviews with stakeholders, review of relevant documents, and focus group discussions involving various community elements. Research Conclusion – The proposed empowerment model emphasizes active community participation in various drug-prevention and drug-education activities, as well as collaboration among government, educational institutions, and community organizations. Research Novelty – The novelty of this study lies in the formulation of an empowerment prototype model that integrates five operational stages into a single, systematic development cycle, offering a conceptual contribution to the development of community-empowerment-based P4GN models in other cities with similar characteristics.